Penurunan Kadar Gula Darah Pada Pasien Dm Tipe II Dengan Masalah Keperawatan Ketidak Stabilan Kadar Gula Darah Dipuskesmas Helvetia - Rismaya Ayu Shakila; Rinawati Tarigan (STIKES Columbia Asia Medan, 2025)
Type II diabetes mellitus is a group of metabolic diseases characterized by hyperglycemia, occurring due to abnormalities in insulin secretion, insulin action or both. One of the recommended sports exercises is leg exercises. Diabetic foot exercises are a form of physical exercise for Diabetes Mellitus sufferers of all ages to avoid injuries so that blood circulation in the feet can be facilitated. Foot exercises are movements that train the small muscles of the feet and improve blood circulation in various positions such as sitting, standing or lying down. The purpose of this writing is to discuss diabetes foot exercises which can reduce blood sugar levels in people with Type II Diabetes Mellitus. The writing method uses a descriptive design with a killing process approach. The written results show a decrease in blood sugar levels after carrying out diabetic foot exercises with results before doing 310 mg/dl and after doing 230 mg/dl.